2011
DOI: 10.1002/smll.201002340
|View full text |Cite
|
Sign up to set email alerts
|

Direct Electrodeposition of Graphene Enabling the One‐Step Synthesis of Graphene–Metal Nanocomposite Films

Abstract: A graphene–Au nanocomposite is prepared by a one‐step electrodeposition technique directly from a dispersion containing graphene oxide (GO) and HAuCl4. The electrodeposited graphene and Au particles are assembled into layered nanostructures. The coelectrodeposition technique can be extended to the fabrication of various graphene‐based composites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
200
0
8

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 381 publications
(212 citation statements)
references
References 39 publications
4
200
0
8
Order By: Relevance
“…Most of the existing reports focus on the deposition of nanoparticles of noble metals and oxides, like Au, Pt, Ag and TiO 2 , on the surface of GNSs to impart new functionalities, such as catalytic, energy storage, photocatalytic, sensory and optoelectronic [8][9][10]. Several papers have recently been published on simulation of the GNS/metal (Al, Cu, Ni) interfacial structure and prediction of the mechanical properties of GNS/Al [11][12][13].…”
mentioning
confidence: 99%
“…Most of the existing reports focus on the deposition of nanoparticles of noble metals and oxides, like Au, Pt, Ag and TiO 2 , on the surface of GNSs to impart new functionalities, such as catalytic, energy storage, photocatalytic, sensory and optoelectronic [8][9][10]. Several papers have recently been published on simulation of the GNS/metal (Al, Cu, Ni) interfacial structure and prediction of the mechanical properties of GNS/Al [11][12][13].…”
mentioning
confidence: 99%
“…As shown in Figure 1a, the cathodic peak at À1.3 V was attributed to the electrochemical reduction of GO. The successive increment of reduction current with each cycle demonstrated that the persistent deposition of conductive graphene on GCE surface was achieved [23]. In the presence of AuCl À , the AuNPs was formed by electro-reduction in this process.…”
Section: Electrodeposition Of Aunps-rgo Composite and Characterizationmentioning
confidence: 88%
“…The AuNPs-RGO composite was synthesized by electrochemical reduction [21,23]. The GO was dispersed in carbonate buffer solution (CBS, pH = 9, 0.1 mol L À1 ) by ultrasonication to form 1 mg mL À1 suspension.…”
Section: Fabrication Of the Sensormentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with the vapor deposition, electrodeposition has merits such as only needing simple equipment, easy operation and low cost. Compared with DC deposition, the current density of AC pulsed electrodeposition is higher and the nucleation rate is faster, which promotes grain refinement and is conducive to the formation of nano-materials [4].…”
Section: Introductionmentioning
confidence: 99%